Injury of Muscular but not Cutaneous Nerve Drives Acute Neuropathic Pain in Rats - Zhu, Jie (Neurosci Bull, 2020)
Acute pain is a common complication after injury of a peripheral nerve but the underlying mechanism is obscure. We established a model of acute neuropathic pain via pulling a pre-implanted suture loop to transect a peripheral nerve in awake rats. The tibial (both muscular and cutaneous), gastrocnemius–soleus (muscular only), and sural nerves (cutaneous only) were each transected. Transection of the tibial and gastrocnemius–soleus nerves, but not the sural nerve immediately evoked spontaneous pain and mechanical allodynia in the skin territories innervated by the adjacent intact nerves. Evans blue extravasation and cutaneous temperature of the intact skin territory were also significantly increased. In vivo electrophysiological recordings revealed that injury of a muscular nerve induced mechanical hypersensitivity and spontaneous activity in the nociceptive C-neurons in adjacent intact nerves. Our results indicate that injury of a muscular nerve, but not a cutaneous nerve, drives acute neuropathic pain.